Conjugated nitroxides. (1st February 2022) - Tretyakov, Evgeny V.; Ovcharenko, Victor I.; Terent'ev, Alexander O.; Krylov, Igor B.; Magdesieva, Tatiana V.; Mazhukin, Dmitrii G.; Gritsan, Nina P.
Abstract: In recent years, research dealing with organic paramagnetic compounds such as stable radicals and high-spin systems has been focused on applied aspects. Several key trends have formed in the application and, hence, in the function-oriented synthesis of organic radicals and polyradicals. This review addresses one of such trends in which the dominant role is played by so-called conjugated nitroxides. Their specific feature is the presence of any unsaturated moiety (C=C, C=N or C=O multiple bond; aromatic or heteroaromatic ring; fused polyaromatic system) adjacent to the nitroxide group. The achievements of the chemistry of conjugated nitroxides are presented, and their physicochemical properties, magneto-structural correlations and practical applications are discussed. The bibliography includes 641 references.